Anesthesia Considerations and Infection Precautions for Trauma and Acute Care Cases During the COVID-19 Pandemic: Recommendations From a Task Force of the Chinese Society of Anesthesiology. (August 2020) - Gong, Yahong; Cao, Xuezhao; Mei, Wei; Wang, Jun; Shen, Le; Wang, Sheng; Lu, Zhijie; Yu, Chunhua; Che, Lu; Xu, Xiaohan; Tan, Juan; Ma, Hong; et al.
Abstract : Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread worldwide. During the ongoing COVID-19 epidemic, most hospitals have postponed elective surgeries. However, some emergency surgeries, especially for trauma patients, are inevitable. For patients with suspected or confirmed COVID-19, a standard protocol addressing preoperative preparation, intraoperative management, and postoperative surveillance should be implemented to avoid nosocomial infection and ensure the safety of patients and the health care workforce. With reference to the guidelines and recommendations issued by the National Health Commission and Chinese Society of Anesthesiology, this article provides recommendations for anesthesia management of trauma and emergency surgery cases during the COVID-19 pandemic.